Katherine Sonderegger's Systematic Theology, The Doctrine of God, vol. 1 (Minneapolis, Fortress Press, 2015) - Lee, Gregory W. (Journal of reformed theology, 2020)
"Katherine Sonderegger's Systematic Theology, The Doctrine of God, vol. 1 (Minneapolis: Fortress Press, 2015)" published on 27 Mar 2020 by Brill.